D-LINK SOLUTIONS FOR THE ORGANIZATION OF THE EDUCATIONAL PROCESS IN THE FIELD OF INFO-COMMUNICATIONS AND TELECOMMUNICATIONS INFRASTRUCTURE OF DATA PROCESSING CENTERS - Pavel V. Romasevich (Современные информационные технологии и IT-образование, 2018)
The article is devoted to the new structure of the course “Fundamentals of Network Technologies”, which has acquired a complete look in the form of three parts: “Basics of network technologies. Part 1: Data transmission and switching in computer networks"; “Basics of network technologies. Part 2: Wireless Wi-Fi networks”; “Basics of network technologies. Part 3: TCP / IP Technologies”, Each of them is a complete unit of the educational program, containing a detailed description of the subject, reflected in the title, many illustrations and examples of configuration. Consecutive study of each part allows you to get a complete picture of the technologies and devices used in modern networks, as well as learn how to apply knowledge in practice. All parts of the course are available for study on the D-Link distance learning and certification portal. For the first part of the course there is a distant exam, which can be taken from any convenient place at any time. The article also presents the solutions of D-Link Company on the organization of the network infrastructure of Data Processing Centers (DPC), which are created in higher educational institutions to accommodate educational resources and support research. The devices correspond to the main market trends: separation of the operating system of the device from its hardware platform, rejection of the use of proprietary silicon, support for Ethernet ports at speeds of 25 Gbit/s and 100 Gbit/s. High network availability is provided by the support of modular hot-swappable power supplies and modular fans.